آليات التمويل الإبتكاري ودورها في تمويل المؤسسات الناشئة –دراسة حالة الوكالة الوطنية لتسيير القرض المصغر والبنك الخارجي الجزائري وكالتي سوق أهراس- - أمال راهم; هدى بن غضاب (My University, 2023)
Through this study,we tried to identify the extent to which financing mechanisms for emerging enterprises are applied in Algeria through an analytical study of the financing mechanisms adopted in the Algerian foreign bank, the Souk Ahras Agency and the Micro Loan Agency.The various formulas developed for financing them, and their importance in financing emerging enterprises .As for the analytical side ,we dealt with the concept of emerging enterprises according to the Algerian legislator the most prominent challenges they face and their prospects, and the most important bodies and mechanisms for supporting and financing emerging enterprises in Algerian .The study concluded that Algerian has established many bodies,agencies ,and programs, and develop supportive strategies for development and development of emerging enterprises and mechanisms for financing them ,in order to activate their vital role and advance them despite the obstacles they face,the most Important of which was the funding problem ,despite their positive contribution to improving many important economic indicators such as providing employment and increasing the gross domestic product However,the Algerian experience in the field of emerging enterprises remains recent and is still far from the advanced stages reached. .................................. حاولنا من خلال هذه الدراسة التعرف على مدى تطبيق آليات تمويل المؤسسات الناشئة في الجزائر،من خلال دراسة تحليلية لآليات التمويل المعتمدة في البنك الخارجي الجزائري وكالة سوق أهراس ووكالة القرض المصغر، ولتحقيق هدف الدراسة تم استعراض الجانب النظري للمؤسسات الناشئة ودورة حياتها وأنواعها،كما تطرقنا إلى تعريف مختلف الصيغ المستحدثة لتمويلها،وأهميتهافي تمويل المؤسسات الناشئة، أما الجانب التحليلي فقد تناولنا فيه مفهوم المؤسسات الناشئة حسب المشرع الجزائري،وابرز التحديات التي تواجهها وآفاقها، واهم هيئات وآليات دعم وتمويل المؤسسات الناشئة في الجزائر،وقد خلصت الدراسةإلىأنالجزائر قامتبإنشاء العديد من الهيئات والأجهزة والبرامج ووضع استراتيجيات داعمة لتطوير وتنمية المؤسسات الناشئة وآليات لتمويلها، وذلك من اجل تفعيل دورها الحيوي،والنهوض بها رغم العوائق التي تواجهها والتي كانت من أهمها مشكلة التمويل، فبرغم من مساهمتها الايجابية في تحسين الكثير من المؤشرات الاقتصادية الهامة كتوفير الشغل، وزيادة الناتج المحلي الإجمالي، وترقية الصادرات الوطنية،وخلق القيمة المضافة،إلا +أنالتجربة الجزائرية في مجال المؤسسات الناشئة تبقى حديثة عهدها ولاتزال بعيدة لحد الآن عن مراحل متقدمة بلغتها بعض الدول. ..................................... A travers cette étude, nous avons essayé d’identifier dans quelle mesure les mécanismes de financement sont appliqués aux institutions émergentes en Algérie. Y compris les mécanismes de financement agréés à la banque algérienne étrangère, agence de souk ahras microcrédit,à travers une étude analytique pour atteindre l’objectif de l’étude , l’aspect théorique des entreprises émergentes, leur cycle de vie et passés en revue, et nous avons également abordé des concepts d’appui définissant les différentes formules dévelopées pour leur financement, et leur importance dans le financement des enterprises émergentes. Les organisms et mécanismes les plus important pour soutenir et financer les enterprises émergentees en Algérie et l’étude a conclu que l’Algérie a établi de nombreux organismes, dispositif programmes et mis en place des stratégies entreprises émergentes et des mécanismes pour les financer, afin d’activer son rôle en obstacles auxquels il est confronté, dont le plus important était le problème de financement,malgré sa contribution il existe de nombreux indicateurs économique importants, tels que la création d’emplois, l’augmentation du produit intérieur brut, la promotion des exportations nationales et la création de valeur ajoutée. Cependant ,l’expérience algériènne dans les secteurs émergents reste récente et encore loin des stades advances attaints par certains.